2014
DOI: 10.1111/1756-185x.12369
|View full text |Cite
|
Sign up to set email alerts
|

IL10 low‐frequency variants in Behçet's disease patients

Abstract: Aim: To explain the missing heritability after the genome-wide association studies era, sequencing studies allow the identification of low-frequency variants with a stronger effect on disease risk. Common variants in the interleukin 10 gene (IL10) have been consistently associated with Behc ßet's disease (BD) and the goal of this study is to investigate the role of low-frequency IL10 variants in BD susceptibility.Methods: To identify IL10 low-frequency variants, a discovery group of 50 Portuguese BD patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These unevaluated variants can have possible effect on BD, and may be responsible for the missing heritability in BD. Indeed, targeted sequencing of ERAP1, MEFV, TLR4, and IL10 in BD patients identified novel population specific functional rare variants strongly associated with BD (Kirino et al, 2013b;Matos et al, 2017). We propose that sequencing of genes with population differentiation estimates higher than their BD associated variants can identify novel BD risk variants, and can contribute to understanding of molecular pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 91%
“…These unevaluated variants can have possible effect on BD, and may be responsible for the missing heritability in BD. Indeed, targeted sequencing of ERAP1, MEFV, TLR4, and IL10 in BD patients identified novel population specific functional rare variants strongly associated with BD (Kirino et al, 2013b;Matos et al, 2017). We propose that sequencing of genes with population differentiation estimates higher than their BD associated variants can identify novel BD risk variants, and can contribute to understanding of molecular pathogenesis of BD.…”
Section: Discussionmentioning
confidence: 91%
“…DNA was extracted as described previously [ 26 ]. Quantification of genomic DNA was performed in triplicate using the Picogreen ® dsDNA Quantitation Kit (Invitrogen, Oregon, USA) in a PerkinElmer top Fluoroscence reader (PerkinElmer, Inc., Waltham, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The strong association of HLA-51 with increased risk of developing BD is well documented (6)(7). In addition, genome wide association studies (GWAS) demonstrated that variants in IL-23R-IL12RB2, and IL-10 are associated with BD susceptibility (8)(9).…”
Section: Introductionmentioning
confidence: 99%